Facilitators and barriers to antiretroviral therapy adherence among HIV-positive adolescents living in Tanzania - Cosette Audi; Ola Jahanpour; Gretchen Antelman; Laura Guay; Mastidia Rutaihwa; Roland van de Ven; Godfrey Woelk; Sarah J. Baird (BMC, 2021)
Abstract Background Adolescents living with HIV face substandard outcomes along the continuum of care, including higher rates of poor adherence and virologic failure. Support groups have been identified as a method to improve adherence, but there is insufficient evidence regarding their effectiveness. This study seeks to examine the protective influences for and barriers to antiretroviral therapy (ART) adherence in HIV-positive adolescents living in Tanzania. Methods This is a qualitative study conducted in Tanzania from January to March 2018. The sample of adolescents aged 10-19 (n = 33) was purposefully selected based on age, gender, and support group attendance to capture a broad range of experiences. Participants completed an in-depth interview, covering topics such as retention in HIV services, support group experiences, and joys and challenges of adolescent life. Interviews were coded and themes related to ART adherence were identified and summarized. Results Support groups helped promote adherence by improving adolescents' knowledge and confidence. Participants associated joining support groups with an improvement in health. Almost every participant described the significant positive influence a treatment supporter had on adherence. Adolescents' daily schedules and emotional state served as a barrier to adherence. Furthermore, adherence was negatively impacted by participants' fear of accidental disclosure. Conclusion Logistical and psychosocial factors can hinder adherence. Interventions that provide both education and psychosocial support, such as peer support groups, have the potential to improve health outcomes for this population, but may not address more persistent barriers to adherence rooted in lack of treatment support from family members or friends who have not been disclosed to, or lack of transportation funds/food security.